Exploring the potential value of improved care for secondary hyperparathyroidism with a novel calcimimetic therapy. (3rd October 2017) - Stollenwerk, Björn; Iannazzo, Sergio; Cooper, Kerry; Belozeroff, Vasily
Abstract: Aims: This study explored the use of a value-based pricing approach for the new calcimimetic etelcalcetide indicated for the treatment of secondary hyperparathyroidism (SHPT) in patients receiving hemodialysis. It used the US payer perspective and applied the cost-effectiveness framework. Because etelcalcetide is an intravenous therapy that can be titrated for individual patients, and because its utilization is yet to be assessed in real world settings, a range of plausible doses were estimated for etelcalcetide to define a range of prices. These were either in relation to the existing oral calcimimetic cinacalcet or compared to no calcimimetic treatment. Materials and methods: The value-based price of etelcalcetide was determined via a Markov model. This model combined data from the etelcalcetide trials and previously published cost-effectiveness models in SHPT, and allowed extrapolation of treatment effects on mortality, cardiovascular events, fracture, and parathyroidectomy. Several dosing scenarios were explored covering the dose ranges of 30.0–64.18 mg per day for cinacalcet and 1.07–3.11 mg per day for etelcalcetide. These included the mean dose from the etelcalcetide trials, the preliminary defined daily dose, and the expected most common dose in real world. An acceptable price range for etelcalcetide was assessed by comparing the incremental cost-effectiveness ratios obtained with the willingness-to-pay threshold range of 100, 000–300, 000/quality-adjusted life-years. Results: Cost-effectiveness analysis supported value-based prices for etelcalcetide ranging from 21.15–49.97/mg vs cinacalcet, and 13.79–119.45/mg vs no calcimimetics. Limitations: There is uncertainty around what the real-world dosing will be for etelcalcetide. Another important nuance is that no studies have examined etelcalcetide effects on hard outcomes and, therefore, this modeling exercise relied on an extrapolation approach. Conclusions: This cost-effectiveness analysis, including scenarios to address uncertainties, allowed estimation of a value-based price range to aid reimbursement decisions in the US.